PROSEDUR PENGOLAHAN PLASTIK DENGAN METODE INJECTION MOLDING - Fahrizal - (Jurnal APTEK, 2009)
We can make two catagories plastic, Thermoplastic and Thermosetting Plastic. Thermoplastic is plastic that did not need any chemical in forming bend and can be meld if it heated and than back to be plastic again. Thermosetting plastic need chemical in forming bend and can not be meld with heat to reformMany processes industry to mak this product. One of that process industry is Injection Molding. Injection Molding is a technique manufactur to make industries product in the production process. The basic element at Injection Molding is the injection section idle and the injector section is activeThe principle of this process is to perform and cooling the liquid in to Mold, afther it cold and freezed, than it can be put out from the mold. Many industries use this process be couse of the huge and fast production capability.